EDUKASI DAN SOSIALISASI PENGELOLAAN SAMPAH ORGANIK DI KELURAHAN KEDAUNG KOTA DEPOK - biandrei, muhamad (Politeknik Negeri Sriwijaya, 2024)
The development of environmental issues is a problem that cannot be separated from socio-political dynamics in Indonesia. This cannot be separated from the link between development in Indonesia and the SDGs (Sustainable Development Goals) international development agenda which was launched in 2015. The issue of household waste is still a problem in Indonesia, especially related to the high number of cases of landfilling of household waste in final landfills, Therefore, community service is carried out to provide general understanding. The Jakarta Veteran National Development University is collaborating with the Depok City government by establishing the Kampung Caraka program to empower the people of Depok City. This program is implemented using observation and field study methods which aim to develop real solutions for handling household waste in Kedaung Village, Depok City, which is based on facts the community's ignorance the usefulness of Maggots for reducing household organic waste. This is the aim of this service through education and outreach. about the potential, technicalities, and various benefits of this project. The results of this program show that there are many people in Kedaung Village who are enthusiastic about the education and outreach program and are interested in developing Maggot BSF media.